To eat or not to eat meat. That is the question - Celada, Paloma; Bastida, Sara; Sánchez-Muni, Francisco J. (Grupo Arán, 2016)
Meat is a well accepted food with appreciable appealing. Due to its high nutritional value it plays a central role in human development. Meat/meat derivates are important sources of proteins, minerals and vitamins. Their nutritional importance is paralleled to their economic impact. Paying attention to the social alarm originated by a recent publication of WHO about the relationship between red and/or processed meat consumption and cancer, this paper reviews the following aspects: a) the present consumption of meat/meat products in Spain; b) the contribution of their macro/micronutrients to the recommended dietary allowances; c) the obliged use of additives (e.g. nitrites and nitrates) to warrant the food safety, and their daily intake. In addition health risks derived from a high consumption, as well as the most appropriate culinary uses in order to reduce the formation of toxic products (e.g. N-nitrosocompounds) are commented. Due to the huge variety of available meat products, this paper concludes that any generalization should be avoided. We also emphasize about the advantages of consuming meat/meat products in the frame of a Mediterranean diet, rich in vegetables, fruits, and bioactive compounds.